Perfluoroalkyl substances and endometriosis-related infertility in Chinese women - Wang, Bin; Zhang, Rongrong; Jin, Fan; Lou, Hangying; Mao, Yuchan; Zhu, Wenting; Zhou, Wei; Zhang, Ping; Zhang, Jun (Environment international, 2017)
Endometriosis is one of the main causes for female infertility. Previous studies suggested that perfluoroalkyl substances (PFASs), a group of ubiquitous environmental chemicals with properties of endocrine disruption and reproductive toxicity, were risk factors for endometriosis but there lacks direct evidence on the possible role of PFASs in endometriosis-related infertility. To fill this gap, we examined the association between PFASs and endometriosis-related infertility among Chinese reproductive-age women in a case-control study, which comprised 157 surgically confirmed endometriosis cases and 178 controls seeking infertility treatment because of male reproductive dysfunction in 2014 and 2015. Blood specimens were collected at the enrollment and analyzed for ten PFASs. Logistic regression was utilized to estimate the adjusted odds ratios (OR) and 95% confidence intervals (CI) for individual PFAS compound. Plasma concentrations of perfluorobutane sulfonic acid (PFBS) were associated with an increased risk of endometriosis-related infertility (second vs. lowest tertile: OR=3.74, 95% CI: 2.04, 6.84; highest vs. lowest tertile: OR=3.04, 95% CI: 1.65, 5.57). This association remained consistent when we restricted to subjects with no previous pregnancy (second vs. lowest tertile: OR=2.91, 95% CI: 1.28, 6.61; highest vs. lowest tertile: OR=3.41, 95% CI: 1.52, 7.65) or to subjects without other gynecologic pathology (second vs. lowest tertile: OR=4.65, 95% CI: 2.21, 9.82; highest vs. lowest tertile: OR=3.36, 95% CI: 1.58, 7.15). Plasma concentrations of perfluoroheptanoic acid (PFHpA), perfluorohexane sulfonic acid (PFHxS) and perfluorononanoic acid (PFNA) were inversely associated with endometriosis-related infertility, but the associations were attenuated in the sensitivity analyses. Our preliminary evidence suggests that exposure to PFBS may increase the risk of female infertility due to endometriosis. Future prospective studies are necessary to confirm these findings. •PFAS exposure is widespread among Chinese reproductive-age women.•We examined the association between PFASs and endometriosis-related infertility.•Exposure to PFBS was associated with the risk of endometriosis-related infertility.